Atividade analgésica do extrato hidroalcóolico e fração acetato de etila da espécie Arrabidaea chica em modelo murino de dor oncológica - BAIMA, Carolina Trovão dos Santos (2024)
Cancer pain is a symptom associated with cancer patients, causing a reduction in quality of life being challenge in palliative care. In the search for potential analgesic drugs, the species Arrabidaea chica shows activity in a model of osteoarthritis, as well as belonging to the list of medicinal plants of interest to the Unified Health System. The aim of this study was to evaluate the activity of the hydroalcoholic extract and the ethyl acetate fraction of the leaves in a cancer pain model with a solid Ehrlich tumor. For the in vivo test, the animals Swiss species were inoculated with tumor cells in the plantar cushion and treated daily for a period of 12 days, orally, and separated into groups according to treatment: with saline, Pregabalin 15mg/kg, Hydroalcoholic extract 250mg/kg and Ethyl acetate fraction 1mg/kg. The animals' body weight and the volume of the paw with the tumor were checked every four days. At these intervals, behavioral tests were carried out to assess spontaneous pain using the Grimace facial ladder and motor activity (open field), as well as assessing mechanical hyperalgesia and thermal stress. At the end of the treatment, the animals were euthanized, their paws were removed for tumor weight analysis and blood was collected for serum cytokine dosage. The results showed that the treatments did not affect the animals' body weight. The tumor increased in volume, but there was no difference between treatment with the extract and fraction and the negative control. However, at the end of the experiment, treatment with the extract was able to reduce the weight of the solid tumor, compared to the group treated with saline. In terms of facial expression and motor activity, the extract and fraction had no significant analgesic effect. When assessing motor activity using the von Frey test, treatment with the species showed a threshold close to normal, but there was no significant difference to the negative control. In the noxious stimulus test using heat stress, the extract showed an analgesic effect similar to the positive control only on the fourth day of treatment. The determination of cytokines showed a reduction in inflammatory cytokines with the treatment of the extract and fraction, with a significant decrease in monocyte chemotactic protein-1 (MCP-1), compared to the negative control. The results show that the presence of the tumor reduces the animals' tolerance to the stimulus of hyperalgesia and treatment with Arrabidaea chica extract and fraction improves activity, especially in the inflammatory period of tumor development (day 4). The cytokine data show that treatment reduces inflammatory cytokines, suggesting a peripheral analgesic mechanism. The study thus demonstrates the potential analgesic effect of the Arrabidaea chica species in a cancer pain model.